Idea powrotu Ormian z rozproszenia do narodowej ojczyzny w świetle memoriałów Roberta Bogdanowicza z 1877 i 1884 roku - Andrzej A. Zięba (Ksiegarnia Akademicka Publishing, 2021)
The idea of the return of Armenians from dispersal to their historicalhomeland in the context of the Robert Bogdanowicz’s memorials from 1877 and 1884